Mononuclear and heterometallic dinuclear, trinuclear and dimer-of-dinuclear complexes derived from single- and double-compartment Schiff base ligands having a less utilized diamine. (17th February 2015) - Chakraborty, Priyanka; Mohanta, Sasankasekhar
Graphical abstract: Syntheses, characterization, crystal structures and diffuse reflectance spectra of two mononuclear copper(II)/nickel(II) and six heterometallic dinuclear Cu II (U VI O2 )/Ni II (U VI O2 ), trinuclear Cu II Cd II Cu II and dimer-of-dinuclear [Cu II Ag I ]2 compounds derived from single-/double-compartment Schiff base ligands, where the aldehyde components are salicylaldehyde, 2-hydroxyacetophenone or 3-ethoxysalicylaldehyde and the diamine component is 2, 2-dimethyl-1, 3-diaminopropane, have been described. A spectroscopic (d–d band of copper(II)) correlation has been highlighted. Abstract: With the aim of exploring metal complexes from single-/double-compartmental acyclic Schiff base ligands having a less utilized diamine counterpart, this work presents the syntheses, characterization, crystal structures and diffuse reflectance spectra of two mononuclear compounds, [Cu II L 1 ]·MeOH and [Ni II L 1 ], and six heteronuclear complexes [Cu II (acetone)L 1 (U VI O2 )(NO3 )2 ]·1.5CH3 COCH3 (1 ), [Cu II (H2 O)L 3 (U VI O2 )(NO3 )2 ]·MeCN (2 ), [Ni II L 1 (U VI O2 )(NO3 )2 ]·CH3 COCH3 (3 ), [{Cu II L 1 Ag I (NO3 )}2 ] (4 ), [{Cu II L 2 Ag I (NO3 )}2 ] (5 ) and [(Cu II L 2 )2 Cd II (ClO4 )2 ] (6 ), where H2 L 1, H2 L 2 and H2 L 3 are the [1+2] condensation products of 2, 2-dimethyl-1, 3-diaminopropane and, respectively, 2-hydroxyacetophenone, salicylaldehyde and 3-ethoxysalicylaldehyde. The crystal structures of [Cu II L 1 ]·MeOH and1 –6 have been determined. Compounds1 –3 are diphenoxo-bridged dinuclear copper(II)/nickel(II)-uranyl(VI) systems, compounds4 and5 are dimer-of-dinuclear [Cu II Ag I ]2 systems where two diphenoxo-bridged dinuclear Cu II Ag I units are interlinked by an Ag I –C (η 2 arene) bond and silver(I)⋯silver(I) interaction (in4 ) or by Cu II ⋯O (nitrate) semi-coordination and silver(I)⋯silver(I) interaction (in5 ), and compound6 is a trinuclear linear Cu II Cd II Cu II system where copper(II) and cadmium(II) are bridged by a bis(μ-phenoxo)-μ-perchlorate moiety. Diffuse reflectance spectra of1 –6 and the corresponding mononuclear copper(II)/nickel(II) compounds have been recorded and it has been explored how much the d–d band position of copper(II) is correlated with the shifting of the copper(II) center from the least-squares basal plane. Salient features in the structures have been discussed.